Influence of two remineralizing agents on bleached enamel surface morphology and mineral composition - An In Vitro study - Malasha Godinho; Ida de N de Ataide; Rajan Lambor; Marina Fernandes (Wolters Kluwer Medknow Publications, 2022)
Aim: To investigate the effects of bleaching with 35% hydrogen peroxide on the structure of tooth enamel and the role of two remineralizing agents for their potential to remineralize any damaged regions of enamel. Materials and Methods: Freshly extracted 32 mature permanent central incisors were selected and sectioned at the level of the cemento-enamel junction. The teeth were divided into four groups consisting of eight teeth each: No bleaching (control) [Group 1], bleaching with 35% hydrogen peroxide [Group 2], bleaching with 35% hydrogen peroxide followed by application of casein phosphopeptide amorphous calcium phosphate fluoride paste [Group 3], and bleaching with 35% hydrogen peroxide followed by application of xylitol-coated calcium phosphate fluoride varnish [Group 4]. The enamel surfaces were analyzed under the scanning electron microscope and quantitative energy dispersive X-ray analysis. Results: Results were statistically analyzed by one-way analysis of variance and Tukey's posthoc test. Group 2 revealed changes in enamel surface morphology and a statistically significant decrease in mineral content. Groups 3 and 4 showed statistically significant remineralization potential. Intergroup comparison showed that samples in Group 4 had a higher mineral content compared to Group 3. Conclusions: The application of the tested remineralizing agents following bleaching was effective in repairing the enamel surface morphology with higher efficacy for the fluoride varnish product. Since bleaching regimes with high concentrations of hydrogen peroxide adversely affect the enamel surface, these findings can translate to clinical practice to reduce the long-term damaging effects of tooth bleaching.